Maestría en educación rural centroamericana: hacia un modelo pedagógico flexible - Carvajal Jiménez, Vivian (2008)
Program in Rural Education” is presented to the national and international community as a high level graduate program, whose purpose is to improve the quality of formal and informal educational processes within the area through an innovative pedagogical model that includes itinerancy along the isthmus, as well as in site and distance learning with a virtual component. Furthermore, this program bases its practice on the development of a flexible model, on inclusiveness and also on a differentiated methodological and evaluative proposal that recovers the knowledge produced in every country around de issue of rural education.